APPLICATION OF MURI Q (MURATAL RHYTHM TONE) METHOD ON LEARNING TAHFIDZ AL-QUR'AN IN JUNIOR HIGH SCHOOL AL-HADI MOJOLABAN SUKOHARJO - Safitri, Nur Ayu; Inayati, Nurul Latifatul (Muhammadiyah University Press, 2019)
This recent research was aimed to answer the following problems: How to apply the Muri Q method on the learning of Tahfidz Al-Qur'an in SMP Islam Al-Hadi Mojolaban and what are the problems faced during the action the Muri Q method on the study of Tahfidz Al-Qur'an. This research is classified as qualitative research types. Data collection methods used by researchers are observation, interviews, documentation, data analysis through three ways: data reduction, data presentation, and conclusions.The results of the analysis of data obtained can be concluded, that application of Muri Q method on the leaning of Tahfidz Al-Qur'an in SMP Islam Al-HadiMojolaban is felt effective and good to improve the memorization of the Qur'an students. Application of Tahfidz Learning with Muri Q method that uses tone is easily memorized by all groups. The application of Tahfidz learning using the Muri Q method can motivate students to memorize to improve memorization to reach the target as a requirement of graduation. Problems encountered in the application of the method of Muri Q in Tahfidz study two problems were identified as internal factors and external factors.